Assessing statistical similarity in dietary intakes of women of reproductive age in Bangladesh - Wable, Gargi; Dickin, Katherine; Kanbur, Ravi; Menon, Purnima; Rasmussen, Kathleen M.; Hoddinott, John F. (Wiley, 2021)
Women of reproductive age (WRA) need adequate nutrient intakes to sustain a healthy pregnancy, support fetal growth, and breastfeed after childbirth. However, data on women's dietary intake in low‐ and middle‐income countries (LMICs) are limited, and assessment of differences between dietary intakes of pregnant or lactating women compared with that of nonpregnant, nonlactating (NPNL) women is untested. Using single, multiple‐pass 24‐h dietary recall data from a sample of WRA residing in rural Bangladesh, we examined women's dietary intakes for energy, protein, calcium, iron, vitamin A, and dietary diversity for three groups: NPNL (n = 2,903), pregnant (n = 197), and lactating women (n = 944). We used equivalence testing to examine similarity in adjusted intakes for pregnant versus NPNL women and lactating versus NPNL women with a predetermined equivalence threshold based on recommendations specific for each reproductive stage. On average, both pregnant and lactating women had insufficient intakes for all dietary measures. Although statistically significant differences were observed between pregnant and NPNL women for energy intake and dietary diversity and between lactating and NPNL women for energy and protein intake, the magnitudes of these differences were too small to reject equivalence. Statistical similarity was also evident in all micronutrients and dietary diversity for both two‐group comparisons. Understanding statistical differences and similarities between dietary measures of women in distinct reproductive stages has important implications for the relevance, appropriateness, and evaluation of maternal diet‐enhancing interventions in LMICs, especially during pregnancy and lactation, when demand for macronutrients and micronutrients is elevated.